Cancer mortality in an Italian rubber factory. Issue 3 (March 1987) - Bernardinelli, L; de Marco, R; Tinelli, C
Abstract : The purpose of the study was to describe the mortality experience of an Italian cohort of rubber workers and an attempt was made to identify any occupational cancer hazards that might currently be affecting men employed in this type of work. A total of 4917 male workers who first started working in a large rubber factory between 1962 and 1972 have been followed up until 31 January 1983. The number of deaths from all causes and from malignant neoplasms was determined and compared with the expected number of deaths calculated from mortality rates for the province in which the population of the plant lived. Mortality from all causes was 85% of that expected. A slight overall excess of deaths from cancer (SMR = 119) was found; this was entirely due to the excess mortality in the 35-44 age group. In order further to evaluate the possible existence of a cancer risk SMRs were analysed by duration of exposure, time since first exposure, and for specific sites of cancer. A trend in SMR with duration of exposure was found for employees with 10 years of follow up or more. A high risk for some tumour sites emerged.